Interaksi Sosial dan Interaksi Virtual Terhadap Variasi Bahasa Generasi Z di Media Digital: Kajian Pragmatik - Farhan, Muhammad Ya'mar; Irham, Muhammad; Antoni, Isnayla Putri; Ghazali, Raudlotul Jannah Al; Wildana, Novan; Anhar, Anhar (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyse the language variations of Generation Z in face-to-face social interactions and virtual interactions on digital media from a pragmatic perspective. The study focuses on platforms widely used by Generation Z, namely TikTok, Instagram, and Twitter/X. The study uses a descriptive qualitative method with a virtual ethnographic approach. Data was collected through participant observation, note-taking techniques, and in-depth interviews with 15 informants aged 18–24 years. In addition, data was collected from posts, comments, and forms of digital interaction that represent Generation Z's distinctive language use. Data analysis was carried out through the stages of data reduction, grouping of linguistic units, interpretation of speech context, and drawing conclusions based on the pragmatic functions of speech, such as intent, implicature, and communication strategies used. The results of the study show that Generation Z's language variation is formed through dynamic interactions between offline and online social spaces. Terms such as FYP, POV, Reels, OOTD, sender, and retweet have undergone shifts in meaning and function to become slang that is expressive, creative, and contextual. This language variation serves as a marker of group identity, a means of social solidarity, and an adaptive strategy in digital communication.